Growth Performance, Fasting Plasma Glucose and Lipid Profile of Sprague-Dawley Rats Fed Different Levels of Omani Halwa - Ali, Amanat; Al-Zuhaibi, Khalid M.; Waly, Mostafa I.; Sankar, D.; Johnson, Eugene H. (Pakistan Journal of Nutrition, 2015)
Omani halwa is a traditional sweet delicacy. The present study evaluated the effects of feeding different levels of Omani halwa on the growth performance, fasting plasma glucose, glycated hemoglobin (HbA1c) and plasma lipid profile of Sprague-Dawley rats. Forty two, 4 weeks old male SD-rats were randomly divided into 7 groups containing 6 rats in each. Six experimental diets, (in which the normal rat chow was replaced with either white or black Omani halwa at 10, 15 and 20% level), were prepared and fed for 10 weeks. The group fed on rat chow acted as control. No significant (p